PELATIHAN MEMBUAT INSEKTISIDA NABATI SEBAGAI PENGENDALI HAMA TANAMAN CABAI RAMAH LINGKUNGAN - Joko Santosa, Sartono; Maulida, Elly Istiana; Widiastuti, Aprilia Putri (Jurnal Pengabdian Masyarakat Sabangka, 2024)
Title PKM: Training on Making Botanical Insecticides as Environmentally Friendly Chili Pest Control involving the Taru Mulyo Farmers' Group in Karangpalem village, Kedawung sub-district, Sragen district which cares about environmental preservation, was held on May 27 2023. The purpose of this activity is to provide training in making vegetable insecticides as pest control for chili plants that are environmentally friendly. Thus the environment becomes clean and healthy, and able to make their own vegetable insecticides. Environmentally friendly chili pest control is a good solution in sustainable agriculture. Dependence on chemical pesticides that are not environmentally friendly, can be replaced by making vegetable insecticides. Besides being cheap and easy to manufacture, it also does not cause problems with the environment. This method can be a feature of local wisdom in controlling pests on the plants it cultivates. The output targets are Sinta accredited scientific journals and presentations at Senadimas. To realize the output target, the methods applied include counseling, training, mentoring and at the same time direct practice. In order for this partnership program to be sustainable, regular monitoring and evaluation is carried out.